2004
DOI: 10.1590/s0102-05362004000200013
|View full text |Cite
|
Sign up to set email alerts
|

Production, quality and water use efficiency of processing tomato as affected by the final irrigation timing

Abstract: A field study was conducted under "Cerrado" conditions of Brazil, during the dry season of 2000, to evaluate the effect of final irrigation timing on fruit yield, quality, and the use of water in processing tomatoes. Fourteen irrigation cut-off times were employed, 7 days apart, from blossom until harvest. Maximum marketable fruit yield took place when irrigations were cut-off 21 days before harvest (10% of red fruit). Total soluble solids content was linearly reduced at the rate of 0.34 ºBrix per each additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…The SMS-treated plots had significantly higher soil-water tension values at 6-inch depths in June and July 2016 compared with the VegApptreated plots but there were no differences between the two treatments at 10-or 14-inch depths for the same time period. This may be because of the relatively shallow placement of the porous tip of the tensiometers (6-8 inches deep), which could result in increasing demand for water at shallower depths compared with the VegApp (Marouelli and Silva, 2007;Marouelli et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The SMS-treated plots had significantly higher soil-water tension values at 6-inch depths in June and July 2016 compared with the VegApptreated plots but there were no differences between the two treatments at 10-or 14-inch depths for the same time period. This may be because of the relatively shallow placement of the porous tip of the tensiometers (6-8 inches deep), which could result in increasing demand for water at shallower depths compared with the VegApp (Marouelli and Silva, 2007;Marouelli et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A lâmina de água aplicada por irrigação, medida por coletores de 1.500 mL, posicionados em cada subparcela, foi a suficiente para elevar a umidade do solo à capacidade de campo (6 kPa), na camada correspondente à profundidade efetiva do sistema radicular. As irrigações foram paralisadas quando 50% dos frutos atingiram a maturação (Marouelli et al, 2004).…”
Section: Methodsunclassified
“…DI, in fact, can be used both to save water and also to improve the quality of some products; nevertheless, special attention must be given when stress was induced, because the water deficit in sensitive phenological phases (such as flowering) can reduce the content of sugars, acids, and carotenoids (Ripoll et al, 2016). Different authors observed how DI increased the content of lycopene, vitamin C, and β-carotene (Favati et al, 2009; Patanè and Cosentino, 2010; Patanè et al, 2011; Chen et al, 2013), regardless of dependence on period and the degree of water stress (Pulupol et al, 1996; Nuruddin et al, 2003; Marouelli et al, 2004; Favati et al, 2009). DI could, therefore, be considered a useful tool to increase in tomato fruits the content of these nutrients (Juroszek et al, 2009), although it reduces the yield (Nuruddin et al, 2003; Marouelli et al, 2004).…”
Section: Water Stress and Produce Qualitymentioning
confidence: 97%